A new paradigm of economic policy based on the synthesis of orthodox and heterodox economics - Horodecka, Anna; Vozna, Liudmyla (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The article challenges the economic policy based only on mainstream economics and asserts the necessity of the elaboration of new approach to economic policy based on the synthesis of orthodox and heterodox economics. It presents some key ideas of heterodox economics, which can fill gaps of mainstream economics. The article regards issues such as sustainable growth, the problem of poverty, rationality and motivation of economic actors from the point of view of ecological, humanistic, feminist, institutional and behavioral economics respectively. The new approach should be based on the complexity and evolutionary approach, according to which the economic system is a part of the bigger meta-system, and, thus, the goals of economic policy should respect the meta-goal of the state policy related to the survival of the society and its natural, social and ethical environment
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 489, s. 137-148
Keywords: economic policy; heterodox economics; goals of economic policy; complexity; paradigm